Mitochondrial DNA diversity and origin of indigenous pigs in South China and their contribution to western modern pig breeds - Chen Wang; Yao-sheng Chen; Han Jianlin; De-lin Mo; Xiu-jin Li; Xiao-hong Liu (Elsevier, 2019)
Indigenous pigs in South China are valuable genetic resources with many specific and unique characters, which have played an important role in the establishment of some western modern pig breeds. However, the origin and genetic diversity of indigenous pigs in South China have not been fully understood. In the present study, we sequenced 534 novel mitochondrial DNA (mtDNA) D-loop and assembled 54 complete mitogenome sequences for all 17 indigenous pig breeds from Fujian, Guangdong, Guangxi and Hainan in South China. These data were analyzed together with previously published homologous sequences relevant to this study. We found that all 13 coding genes of the mitogenomes were under purifying selection, but ND1 had the most variable sites and CYTB contained the most non-synonymous SNPs. Phylogenetic analysis showed that all indigenous pigs in South China were clustered into the D haplogroup with D1a1, D1b, D1c and D1e sub-haplogroups found to be dominant. Haplotype and nucleotide diversities of D-loop sequences ranged from 0.427 to 0.899 and from 0.00342 to 0.00695, respectively, among which all pigs in Guangdong had the lowest diversity. The estimates of pairwise FST, gene flow (Nm) and genetic distance (Da) indicated that most of these indigenous pig breeds differentiated from each other significantly (P<0.05). Among the western modern breeds, Berkshire and Yorkshire had significant Asian matrilineal footprints from indigenous pigs in South China, especially the Spotted pigs distributed in Guangdong and Guangxi. The neutrality test (Fu's FS) indicated that indigenous pigs from Fujian and Guangxi had gone through recent population expansion events (P<0.05). It is concluded that indigenous pigs in South China were most likely derived from the Mekong region and the middle and downstream regions of Yangtze River through Guangxi and Fujian. Our findings provide a complete and in-depth insight on the origin and distribution pattern of maternal genetic diversity of indigenous pigs in South China.